Involvement of HHV-4 (Epstein–Barr virus) and HHV-5 (cytomegalovirus) in inflammatory bowel disease and colorectal cancer: a meta-analysis - Marongiu, Luigi; Venturelli, Sascha; Allgayer, Heike (Cancers, 2022)
Gastrointestinal diseases (GDs) include colorectal cancer (CRC), gastric cancer (GC), and inflammatory bowel disease (IBD). CRC and GC are typically diagnosed at later stages of development, reducing patients’ chances of survival. IBD is characterized by chronic intestinal inflammation and is a significant risk factor for the development of CRC. Chronic bacterial infections have been shown to promote some GDs, but the role of viruses in the etiology of these diseases is less clear. The present meta-analysis retrieved literature on the viral prevalence in GD patients, measuring the GD risk in odd ratios. By quantifying the study heterogeneity, the literature bias was fundamentally included in the analysis. The analysis also included 11 metagenomic studies. Our meta-analysis retrieved 11,413 studies, with 196 suitable for analysis. HHV-4 (Epstein-Barr virus) was identified as a significant risk factor for the development of IBD, and HHV-5 (cytomegalovirus) as a risk factor for both CRC and IBD. Polyomaviruses and the Hepatitis B virus were also, less strongly, involved in the risk of CRC and IBD. No relations withstanding the literature bias were identified for GC. The study discusses these findings, as well as the role of other viruses in the etiology of CRC and IBD.